Ethical decision making in academic dishonesty with application of modified Theory of Planned Behavior: a review - Chan, Ling Meng; Othman, Jamilah; D’Silva, Jeffrey Lawrence; Omar, Zoharah (Canadian Center of Science and Education, 2014)
This conceptual paper studies the application of the Theory of Planned Behavior (TBP) in academic dishonesty with the mediating variable of ethical ideologies. The study reviews literature on the Theory of Planned Behavior and past studies pertaining to academic dishonesty. The paper analyses the relationship of the variables of TPB on academic dishonesty with ethical ideologies. A conceptual research framework is presented; it provides insight into predicting and understanding how academic dishonesty can occur. The framework suggests that ethical ideology is significantly strengthened by the application of TPB in understanding and predicting how academic dishonesty occurs. Given that ethical ideology provides guidance in judging right and wrong, duty, obligation and moral responsibility, it is an appropriate tool for the researcher, who needs better understanding to diagnose the influences of ethical ideology on unethical behaviour.